2004
DOI: 10.1176/appi.ajp.161.5.918
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Sexual Maturation During Long-Term Treatment With Risperidone

Abstract: In this retrospective analysis, there was no evidence of statistically or clinically significant growth failure or delay in pubertal onset or progression in children treated for up to 1 year with risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 7 publications
1
22
0
2
Order By: Relevance
“…The group with hyperprolactinemia did not differ in pubertal stage from the group without hyperprolactinemia. An earlier 1-year follow-up study of mainly male (80%) children with DBD (n = 222, mean age 11.9 ± 1.4 years) starting prolactin-elevating medication showed no difference in the progression of stages of puberty [24]. When we compared the data of our total study group in attaining the 50th percentile of Tanner stage of puberty with the normative data, the adolescents in the present study were 1.6 years late.…”
Section: Discussionmentioning
confidence: 99%
“…The group with hyperprolactinemia did not differ in pubertal stage from the group without hyperprolactinemia. An earlier 1-year follow-up study of mainly male (80%) children with DBD (n = 222, mean age 11.9 ± 1.4 years) starting prolactin-elevating medication showed no difference in the progression of stages of puberty [24]. When we compared the data of our total study group in attaining the 50th percentile of Tanner stage of puberty with the normative data, the adolescents in the present study were 1.6 years late.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperprolactinemia is usually transient in nature (Findling et al, 2003), but should be closely monitored because of its potential impact on growth and sexual maturation. A recent meta-analysis, however, concluded that there was no evidence of statistically or clinically significant growth failure or delay in pubertal onset or progression in children during risperidone treatment for up to 1 year (Dunbar, Kusumakar, Daneman, & Schultz, 2004). Metabolic AEs such as glucose dysregulation or lipid abnormalities can be related to weight gain or occur independently.…”
Section: Discussionmentioning
confidence: 99%
“…22,33,34 In the analysis of safety of its use for long periods of time, five studies investigated the use of risperidone in a total of 700 children and adolescents aged 5 to 15 years and found no influence on growth or sexual maturity, although there were changes in the levels of prolactin. 35 A retrospective study including 80 individuals with autism who used risperidone to control aggression or impulsivity found that over 60% had a positive result after six months of treatment. The most common adverse effect was weight gain, followed by drowsiness, the adverse event most often associated with treatment discontinuation.…”
Section: Risperidonementioning
confidence: 99%